ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA MINAT LANJUT PENDIDIKAN PADA MASYARAKAT DI DESA PEDUSAN RT 59 KECAMATAN SEDAYU KABUPATEN BANTUL - Najla Afiqotul Wafa (JURNAL TEKNOLOGI PENDIDIKAN, 2024)
Based on the results of research conducted by researchers regarding the factors that influence the low interest in continuing education in the community in Pedusan Village, RT 59, Sedayu District, Bantul Regency, it can be concluded as follows: 1. The view of education depends on the background of the village community, 2. There is no community interest and motivation to continue their education to tertiary level, 3. The main factor in the low interest in continuing education is the economic factor of the village community, apart from that there are other factors such as the lack of support from parents and the lack of community knowledge about the importance of education for the future . The aim of this research is to determine the factors that influence the low interest in further education. From the results of research that has been carried out, the majority of the people in Pedusan Village only have high school graduates, they are reluctant to continue their education to college. This problem occurs due to several factors such as motivation factors and community conditions. The method used by researchers is to use a qualitative approach, a qualitative case study type of research. To collect data for this research, the author used data sources in the form of documents, observations and interviews.